2020
DOI: 10.1007/s10237-020-01369-6
|View full text |Cite|
|
Sign up to set email alerts
|

Multiscale characterization and micromechanical modeling of crop stem materials

Abstract: An essential prerequisite for the efficient biomechanical tailoring of crops is to accurately relate mechanical behavior to compositional and morphological properties across different length scales. In this article, we develop a multiscale approach to predict macroscale stiffness and strength properties of crop stem materials from their hierarchical microstructure. We first discuss the experimental multiscale characterization based on microimaging (micro-CT, light microscopy, transmission electron microscopy) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 67 publications
0
40
0
Order By: Relevance
“…The first part of this equation directly comes from the incremental form of the principle of maximum plastic dissipation outlined in (41). Similarly, the second part is the incremental form of the Helmholtz free energy rate defined in (31).…”
Section: Discrete Form Of the Materials Optimization Problemmentioning
confidence: 99%
See 2 more Smart Citations
“…The first part of this equation directly comes from the incremental form of the principle of maximum plastic dissipation outlined in (41). Similarly, the second part is the incremental form of the Helmholtz free energy rate defined in (31).…”
Section: Discrete Form Of the Materials Optimization Problemmentioning
confidence: 99%
“…including all constraints defined through the stress admissible set E Σ n+1 and microscale design admissible set E ad . The first two conditions are essentially the elastoplastic constitutive equations relating the macroscale stress with the macroscale strains via (39) and the constraint on the macroscale stress defined through the homogenized yield criterion (41). The third condition is the definition of the Helmholtz free energy in terms of microscale design variable m x,j n+1 .…”
Section: Discrete Form Of the Materials Optimization Problemmentioning
confidence: 99%
See 1 more Smart Citation
“…Small grain cereals lose a high percentage of their yield through lodging (buckling of the stems near ground level) before harvesting due to the weak structure of the stem, especially under heavy rain and wind (1). Computational models are being used to simulate stem collapse under loads to better understand the relationship between the stem's structure and its strength (2). With this understanding, the stem's structure can then be modi ed through conventional breeding or genetic engineering to increase its resistance against lodging.…”
Section: Introductionmentioning
confidence: 99%
“…Continuum micromechanics-based homogenization has been successfully applied to describe natural multiscale systems such as wood, bone, or cement (Fritsch and Hellmich 2007;Fritsch et al 2009;Pichler and Hellmich 2011;Morin et al 2017;Hofstetter et al 2005). In our recent work (Gangwar and Schillinger 2019;Gangwar et al 2020), we showed that continuum micromechanics models can accurately predict both linear elastic and inelastic behavior of plant materials. We also demonstrated that each hierarchical level can be statistically characterized through microimaging techniques.…”
Section: Introductionmentioning
confidence: 99%